The Digital Banking Revolution : How Fintech Companies are Transforming the Retail Banking Industry Through Disruptive Financial Innovation - Wewege, Luigi; Thomsett, Michael C. (De Gruyter, 2019)
Emergent innovative financial technologies are profoundly changing the way in which we spend, move and manage our money, unlike ever before, and traditional retail banks are facing stiff competition. The global financial crisis in 2007-2009 led to large losses, and even the collapse of a significant number of established banks shaking the trust of financial customers worldwide. The Digital Banking Revolution is an insightful look at how financial technology and the rapid rise of financial technology companies have brought welcome changes offering flexibility to the banking industry. The book offers a unique perspective on the consumerization of retail banking services. It delves into the many changes that financial innovations have brought about in banking, the main financial disruptors, the new era of "banking on the go," and financial innovations from countries around the world before concluding with a discussion on the future of banking including optimizing structures, new strategies for business outcomes, and human resources in the digital era.